2012
DOI: 10.1021/am300089f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optoelectronic Properties of Two-Dimensional FeS2 Nanoplates

Abstract: There is a growing interest in the earth abundant and nontoxic iron disulfide (FeS(2)) photovoltaic materials. Here, we report the synthesis of FeS(2) nanoplates with different spectral features which we have associated with thicknesses and crystallization. The structure and crystalline order of ultrathin FeS(2) nanoplates have a strong influence on the carrier lifetime, electronic and optical properties. We demonstrate that two-dimensional FeS(2) nanoplates show great promise for fabrication of hybrid bulk he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 20 publications
2
71
0
Order By: Relevance
“…For example, FeS2 tend to grow in three dimensions, but two-dimensional FeS2 nanoplates have been reported. 51,52 Thus, certain synthesis parameters force the NCs to grow in a non-energetically favored shape and yield two-dimensional structures. What drives this anisotropic growth?…”
Section: Figure 1: Evolution Of the Gibbs Free Energy Of A Cluster Vementioning
confidence: 99%
“…For example, FeS2 tend to grow in three dimensions, but two-dimensional FeS2 nanoplates have been reported. 51,52 Thus, certain synthesis parameters force the NCs to grow in a non-energetically favored shape and yield two-dimensional structures. What drives this anisotropic growth?…”
Section: Figure 1: Evolution Of the Gibbs Free Energy Of A Cluster Vementioning
confidence: 99%
“…It can also be observed that elemental sulphur and FeCl 2 were employed as the sulphur and iron precursors, in the majority of the reported experiments. Only some cases used iron pentacarbonyl 70 and FeBr 2 (ref. 71) as iron precursors.…”
Section: -69mentioning
confidence: 99%
“…In our lab, we have also taken to utilizing the hot injection method for pyrite nanocrystal synthesis [24,54]. It has been observed that both cubes and nanospheres can be made for pyrite nanomaterial, but from the use of different synthetic routes.…”
Section: Hot Injection Synthesismentioning
confidence: 99%